2022
DOI: 10.3390/jal2020008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Exercise on Sleep Quality in Elderly Adults: A Systematic Review with a Meta-Analysis of Controlled and Randomized Studies

Abstract: Introduction: Aging is directly related to sleep problems. Primary insomnia has a negative impact on the lives of elderly adults, altering cognitive and metabolic functions. Physical activity is positively related to improvement in sleep quality. The objective of this systematic review was to analyze the effects of physical activity programs in healthy elderly individuals aged 60 years or older, using the Pittsburgh Sleep Quality Index (PSQI) as a tool. Methods: The search was performed in the PubMed and Sciel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
1
4
0
1
Order By: Relevance
“…This may be explained by the physical training effects in the active group. Previous reports suggest a beneficial role of chronic training schedule on inhibitory function (68,69), processing speed (70), insomnia, daytime sleepiness, and sleep quality (71,72). Furthermore, from before to during RDIF, our results showed an improvement in the majority of cognitive function variables for the active group, including attention, executive function, inhibition, recognition memory, and associative memory; there were no changes for other cognitive domains including processing speed and associative learning.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This may be explained by the physical training effects in the active group. Previous reports suggest a beneficial role of chronic training schedule on inhibitory function (68,69), processing speed (70), insomnia, daytime sleepiness, and sleep quality (71,72). Furthermore, from before to during RDIF, our results showed an improvement in the majority of cognitive function variables for the active group, including attention, executive function, inhibition, recognition memory, and associative memory; there were no changes for other cognitive domains including processing speed and associative learning.…”
Section: Discussionsupporting
confidence: 49%
“…This may be explained by the physical training effects in the active group. Previous reports suggest a beneficial role of chronic training schedule on inhibitory function ( 68 , 69 ), processing speed ( 70 ), insomnia, daytime sleepiness, and sleep quality ( 71 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ The association between physical activities and sleep quality was exclusively reported in 18 articles [3,4,13,16,18,[26][27][28][30][31][32][33][35][36][37]39,40], while five articles reported an association between physical activities and insomnia and other sleep disorders [15,20,29,38,41]. In all articles, physical activity was positively associated with sleep quality, which indicates that physical activities improve sleep quality.…”
Section: Crosssectional Studymentioning
confidence: 94%
“…Of the articles reporting associations between physical activities and insomnia and other sleep disorders [15,20,29,38,41], one reported that physical exercise had a positive impact on both the insomnia group of elderly adults (standardized mean difference (SMD): -0.57; 95%CI: -0.73 to -0.4; p < 0.001; I2 = 53%), noninsomnia group (SMD: -0.61; 95% CI: -0.75 to -0.47; p < 0.00001; I2 = 73%), and both groups combined (SMD: -0.59; 95%CI: -0.70 to -0.49; p < 0.0001, I2 = 68%) [29]. A study conducted on adults with insomnia found that both physical exercise and mind-body exercise interventions led to similar improvements in subjective sleep quality, and short-term interventions (lasting three months or less) showed a significantly greater reduction in sleep disturbances compared to long-term interventions (lasting more than three months) [15].…”
Section: Effect Of Physical Activity On Sleep Disordersmentioning
confidence: 99%
“…The statistical power will be calculated using the meta power calculator (available for free on https://jtiebel.shinyapps.io/MetaPowerCalculator/ ). A study is regarded adequately powered if it has a statistical power of 0.8 at a significance level of 0.05[ 21 ].…”
Section: Discussionmentioning
confidence: 99%